Effect of the Motion Correction Technique on Image Quality at 320-Detector Computed Tomography Coronary Angiography in Patients With Atrial Fibrillation. Issue 4 (July 2016) - Tatsugami, Fuminari; Higaki, Toru; Fukumoto, Wataru; Kaichi, Yoko; Iida, Makoto; Fujioka, Chikako; Kiguchi, Masao; Kihara, Yasuki; Awai, Kazuo
Abstract : Objective: Adaptive motion correction (AMC) is a new technique that can suppress blurring of the coronary arteries. We evaluated its effect on the image quality of coronary computed tomography angiography in patients with atrial fibrillation (AF). Methods: Twenty-five patients with persistent AF underwent coronary computed tomography angiography. Axial image data sets were reconstructed with and without AMC and the image noise in the perivascular tissue of the coronary arteries was measured. Two radiologists visually evaluated the overall image quality of the coronary artery segment using a 4-point scale (1, uninterpretable; 4, good). Results: The mean image noise in the perivascular tissue of the right, but not the left coronary artery, was reduced by AMC (43.8 vs 52.5 Hounsfield units; P < 0.01) and the mean image quality score for the right, but not the left coronary artery, was improved by AMC (3.01 vs 2.74; P < 0.01). The image quality scores in patients with a heart rate of 75 to 114 beats per minute tended to be improved by AMC (75–94 beats per minute: P = 0.06; 95–114 beats per minute: P < 0.01); in patients with a heart rate up to 74 or above 115 beats per minute, they were not improved ( P = 0.46 and P = 0.13, respectively). Conclusions: Adaptive motion correction reduced motion artifacts and improved image quality of the right coronary artery in some patients with AF.